2023
DOI: 10.1002/anie.202218369
|View full text |Cite
|
Sign up to set email alerts
|

An Atomically Precise Pyrazolate‐Protected Copper Nanocluster Exhibiting Exceptional Stability and Catalytic Activity

Abstract: The synthesis of atomically precise copper nanoclusters (Cu-NCs) with high chemical stability is a prerequisite for practical applications, yet still remains a long-standing challenge. Herein, we have prepared a pyrazolate-protected Cu-NC (Cu8), which exhibited exceptional chemical stability either in solid-state or in solution. The crystals of Cu8 are still suitable for single crystal X-ray diffraction analysis even after being treated with boiling water, 8 wt % H 2 O 2 , high concentrated acid (1 M HCl) or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…For instance, subtle environmental changes, such as pH, temperature, and salt concentration, can denature natural self-assemblies, such as DNA and enzymes. Similarly, these changes of environmental factors also significantly influence the structural geometry and stability in the field of coordination driven self-assembly. , The lability of these supramolecular constructs has emerged as a major issue in their structural characterization and applications, particularly in fields like catalysis, energy storage, and in vivo diagnosis/therapy …”
Section: Introductionmentioning
confidence: 99%
“…For instance, subtle environmental changes, such as pH, temperature, and salt concentration, can denature natural self-assemblies, such as DNA and enzymes. Similarly, these changes of environmental factors also significantly influence the structural geometry and stability in the field of coordination driven self-assembly. , The lability of these supramolecular constructs has emerged as a major issue in their structural characterization and applications, particularly in fields like catalysis, energy storage, and in vivo diagnosis/therapy …”
Section: Introductionmentioning
confidence: 99%
“…6,11 For example, Lee and coworkers reported that the alloyed M 1 Au 24 (M = Pt, Pd) nanoclusters showed enhanced HER performances relative to the parent Au 25 nanoclusters. 49 The Jin group gave another evidence that the current density of doped Au 36 Ag 2 (SR) 18 was 5.1 times higher than that of undoped Au 38 (SR) 24 . 50 In this work, considering that the innermost Ag 13 kernel of Ag 29 -BDT could be substituted by the introduced Pt heteroatom and the electronic properties of the cluster would be remarkably altered, we alloyed the homo-silver Ag 29 -BDT into Pt-doped Pt 1 Ag 28 (BDT) 12 (TPP) 4 (Pt 1 Ag 28 -BDT for short).…”
Section: Overall Operationmentioning
confidence: 99%
“…6,[9][10][11][12][13][14][15][16] Due to their quantum size effects and discrete electronic energy levels, metal nanoclusters display size-, structure-, and composition-dependent performances, including optical, electrochemical, magnetic, and chiral properties. [17][18][19][20][21][22][23][24][25] Any perturbations in the composition/structure may induce tremendous changes in the properties of the clusters. Accordingly, compared to large-sized nanoparticles, metal nanoclusters have served as ideal platforms to investigate the structureproperty correlations, especially in designing the former deficiency mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…Metal nanoclusters (M NCs) offer significant advantages, including small size, , low toxicity, , and unique optical , and electrical properties, making them increasingly popular in the electrochemiluminescence (ECL) field. Copper (Cu), which is abundant in the earth’s crust, is an emerging raw material for preparing nanoclusters. However, due to the high reactivity and low standard reduction potential of Cu, achieving stable Cu NCs is an exceptionally difficult task. , Applying ligands to coat Cu NCs is a reliable approach to enhance their stability, but most ligands protecting Cu NCs are limited to biomolecules, such as DNA , and proteins , for this purpose. Utilizing small-molecule ligands to stabilize Cu NCs can effectively diminish the thickness of the insulating layer present on their surface, thereby enhancing the efficiency of carrier transport and, ultimately, augmenting their ECL performance. , Regrettably, Cu NCs protected by small-molecule ligands generally suffer from inadequate solution stability and a propensity to undergo aggregation and stacking phenomena.…”
Section: Introductionmentioning
confidence: 99%